2021
DOI: 10.1016/j.isci.2021.102851
|View full text |Cite
|
Sign up to set email alerts
|

Sensor array and gas chromatographic detection of the blood serum volatolomic signature of COVID-19

Abstract: Volatolomics is gaining consideration as a viable approach to diagnose several diseases, and it also shows promising results to discriminate COVID-19 patients via breath analysis. This paper extends the study of the relationship between volatile compounds (VOCs) and COVID-19 to blood serum. Blood samples were collected from subjects recruited at the emergency department of a large public hospital. The volatile compounds (VOCs) were analyzed with a Gas Chromatography Mass Spectrometer (GC/MS). GC/MS data shows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…37 The main analytical equipment for these VOCs is gas chromatography and mass spectrometers. 38 This was first recognised by Hippocrates around 400 BD, and he reported several disease-specific odours from urine or sputum. The major sources of VOCs include breath, sweat, skin, urine, faeces and vaginal secretions.…”
Section: The Concept Of Volatile Organic Compounds (Vocs)mentioning
confidence: 97%
See 1 more Smart Citation
“…37 The main analytical equipment for these VOCs is gas chromatography and mass spectrometers. 38 This was first recognised by Hippocrates around 400 BD, and he reported several disease-specific odours from urine or sputum. The major sources of VOCs include breath, sweat, skin, urine, faeces and vaginal secretions.…”
Section: The Concept Of Volatile Organic Compounds (Vocs)mentioning
confidence: 97%
“…The complex biochemistry processes of COVID-19 such as SARS-CoV-2 entry and replication, humoral and cellular immunity, and cytokine storm, could induce the formation of VOCs or alter the normal VOCs profiles. 38 Also, the infection leads to a variation of the microbial flora in the lungs and, as a consequence, to a variation of exhaled metabolites. These VOCs are the targets of breath diagnostics and are used to assess health status without being invasive for patients.…”
Section: The Concept Of Volatile Organic Compounds (Vocs)mentioning
confidence: 99%
“…This study found that direct MS analysis of breath VOCs from COVID-19 patients had a 93% accuracy, which could lead to the development of the novel online approaches for large-scale COVID-19 screening [77]. For COVID-19 diagnosis, GC-MS analysis of breath VOC and blood metabolites has been recommended [81,82]. LC-MS has been a widely used technique for determination of exhaled breath condensate (EBC).…”
Section: Covid-19 Virus Detection Using Mass Spectroscopymentioning
confidence: 99%
“…Volatile substances produced by pathogenic viruses like COVID-19 may serve as biomarkers. GC-MS analysis of breath VOC and blood metabolites has been proposed for COVID-19 diagnosis and research ( 26–28 ).…”
Section: Mass Spectrometrymentioning
confidence: 99%